PERGESERAN FUNGSI TARI BESAGU AYU PADA SUKU DAYAK KANTU’ DI KAPUAS HULU KALIMANTAN BARAT - Kornellya, Nelly; Fretisari, Imma; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract Researchers want to explore thoroughly about the function of ritual dance Besagu Ayu who changed functions in the from of dance show.The method used in this research is descriptive method with a form of qualitative research and using ethnocoreology approach. The Data contained in this research is the fact about the process of the traditional ritual of treatment culture of Besagu Ayu Dance owned by the DayakKantu’ tribe in the village of Bika Hulu, Kapuas Hulu district, West Borneo. Data were analyzed qualitatively, with Thiento Yudhi, Tobias Ranggi and Rayun as the interviewees, who know clearly about Besagu Ayu dance of Dayak Kantu'. The data proceeded through the results of observation, interviews and documentation. Mechanical testing the validity of the data using techniques credibility test, and data were analyzed using interviews and field notes in a systematic search for and compile the data obtained.Based on the data analysis, can be summarized as follows. Besagu Ayu dance in Dayak Kantu’ in the District of Kapuas Hulu in West Borneo is a traditional dance of treatment ritual. The dance Besagu Ayu who served in the from of the show just to enjoy by the audiences. Keywords:The Relocation of functions, of Besagu Ayu dance